Microbial composition of livestock buildings is the basis for the creation of a biological preparation to stabilize the microbial background - Aikumys Zhumakayeva; Rakhimtay Tleulessov; Zhanar Bakisheva; Mereke Tokayeva; Sairan Dyussenov; Indira Akzhunussova (Caspian Journal of Environmental Sciences)
The present study investigates the microbial composition within the livestock breeding premises of a cattle breeding farm with a complete technological cycle of agricultural products at JSC "Astana-Onim." The research focuses on the quantitative and qualitative composition of the microbiocenosis, primarily comprising five genera: coliforms, bacilli, lactobacilli, staphylococci, and protozoa. The research methodology included a combination of various approaches, such as observation, analysis, and experimentation. The data collection involved careful sampling and laboratory analysis, enabling a comprehensive assessment of the microbial composition within the livestock breeding premises. The results obtained from this study contribute to a better understanding of the microbial dynamics in such settings, with implications for the sanitation and health management of livestock facilities. Moreover, the study identifies the microbial composition in areas housing both sick and healthy animals. It further identifies representatives of the indigene microflora and takes note of the reaction of lactic acid bacteria. Notably, the growth of colonies on selective media with distinct morphological and cultural properties is observed. In conlusion, Species and quantitative composition of microflora in livestock facilities includes various species and genera; Some notable percentages include Staphylococcus aureus (12%), Bacillus subtilis (12%), Bacillus mucoides (19%), Bacillus mesentericus (6%), total Bacillus genus bacteria (37%), molds (15%), Escherichia coli (5%), Lactobacillus spp. (15%), and Proteus vulgaris (7%).